PROSES PENGHITUNGAN, PENYETORAN, PELAPORAN DAN PENCATATAN PPH PASAL 23 PADA PT. MULTI KARYA SINERGI - Dewi Aprida; Apriza Leony (POLITEKNIK LP3I JAKARTA, 2021)
PPh Article 23, is a tax withheld on income received or earned by domestic taxpayers (individuals and entities), and permanent forms of business originating from capital, rendering services, or carrying out activities other than those deducted from Article 21 Income Tax, Article 23 Income Tax it is paid to be owed by a government agency or domestic Tax Subject, activity organizer, permanent establishment, or other representative of a foreign company. The purpose of this study was to determine the process of calculating, depositing and reporting PPh 23 at PT. Multi Karya Sinergi which acts as a tax cutter for services. This research is in the form of descriptive, namely by classifying and analyzing data so as to provide a solution to a problem by means of field studies consisting of observations, interviews, work practices and literature studies. Based on the results of the study it can be concluded that the calculation of Article 23 PPh is in accordance with the rates and tax bases. For depositing and reporting taxes in 2021, you are already using an application to make it easier to work. Keywords: Income Tax Article 23, Calculation, Deposit